Bram Stoker - Senf, Carol A. (Gothic authors: critical revisions., 2010)
This study of Bram Stoker focuses on Stoker as a Gothic writer. Identified with Dracula, Stoker is largely responsible for taking the Gothic away from medieval castles and placing it at the centre of modern life. The author examines Stoker's contribution to the modern notion of Gothic and thus to the history of popular culture, and demonstrates that the excess generally associated with the Gothic is Stoker's way of examining social economic and political problems. His relevance today is his depiction of problems that continue to haunt us at the beginning of the twenty-first century.